2008
DOI: 10.5194/aab-51-541-2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inbreeding on lean meat percentage and average daily gain in Hungarian Landrace pigs

Abstract: Pedigree and field test data -collected between 1994-2005 -were analyzed in a group of 132,548 Hungarian Landrace pigs. The analysed traits were average daily gain (ADG) and lean meat percentage (LMP). In the present study inbreeding coefficients, pedigree completeness (complete generation equivalents) and inbreeding depression for ADG and LMP were estimated. Increasing the number of generations that were considered in the pedigree the estimated inbreeding coefficients did not change after the 5 th generation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The influence of the inbreeding coefficient on meat productivity indicators is described not only in sheep but also in pigs (Vígh et al, 2008) or beef cattle (Lozada-Soto et al, 2021). There was a statistically significant effect of the inbreeding coefficient on the development of MLD and the thickness of back fat in the work dealing with the effect of inbreeding on meat yield in the Dorper sheep breed, which corresponds to our results.…”
Section: Discussionsupporting
confidence: 87%
“…The influence of the inbreeding coefficient on meat productivity indicators is described not only in sheep but also in pigs (Vígh et al, 2008) or beef cattle (Lozada-Soto et al, 2021). There was a statistically significant effect of the inbreeding coefficient on the development of MLD and the thickness of back fat in the work dealing with the effect of inbreeding on meat yield in the Dorper sheep breed, which corresponds to our results.…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, 10 % increase of the inbreeding coefficient decreased the number of days up to 104.5 kg by 2.1 days. Similarly the growth traits of Hungarian Landrace pigs shoved only a very slight decrease as a result of inbreeding (Vígh et al 2008). The results of the different studies examining the effect of inbreeding on carcass traits (e.g.…”
Section: Inbreeding Depression and Genetic Trendsmentioning
confidence: 93%
“…In pigs, many studies suggested that an increase of the inbreeding coefficient resulted in a significant reduction of reproductive traits, including the TNB, the number of alive piglets at birth (NBA), and gestation length ( Farkas et al 2007 ). In addition, the increased inbreeding negatively affected growth and production performance, such as lean meat percentage, average daily gain, and growth traits at pre- or weaning ( Vigh et al 2008 ; Gowrimanokari et al 2019 ). More recent studies provided significant evidence that TNB was associated with ID in a Korean native pig population ( Kim et al 2019 ) and an Iberian pig population ( Casellas et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%